Phraseology describing behavior in Kazakh and Turkish languages: functional and parametric analysis - Kolpenova А.К. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2022)
The article analyzes qualitative semantic phraseologisms describing human behavior in Kazakh and Turkish languages in a comparative way from functional and parametric aspects. It is formulated that denotative and motivational components in the structure of phraseological meaning reflect the character of phraseologisms as language symbols. Characterized by an evaluative component determined by the criterion «good – bad» through the image, an emotional component measured by the scale « approving-disapproving», and a stylistic component derived from their content. İt is concluded that within the boundaries of «approving-disapproving» emotions such as hatred, reproach, contempt, and mockery take place. Phraseologisms are recognized as the main linguoindicators that allow us to determine general Turkic commonalities and to distinguish between the individuality of each nation recognized. As a result, it is concluded that the evaluative, emotional and stylistic components in the structure of phraseological meaning strengthen the pragmatic potential of phraseologisms and determine their communicative function, and the national-cultural component determines the cognitive function of phraseologisms